2015
DOI: 10.1111/coa.12369
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Performance Status Scale and MD Anderson Dysphagia Inventory as swallowing outcome measures in head and neck cancer: a prospective cohort study

Abstract: This is the first prospective study comparing the MDADI and PSS questionnaires at multiple time points. Our study shows that these different instruments have a good relationship in measuring swallowing function in patients with head and neck cancer in short and medium term after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
3
1
2
Order By: Relevance
“…Additionally, at all study occasions, the difference between the patients and the control group without dysphagia exceeded the suggested threshold (10 points) indicating a clinically important difference 15 . These results are in line with other studies of patients with HNC, where patients with oral and oropharyngeal tumors demonstrated similar values of the MDADI and with a similar pattern of change over time 12,19‐23 . Additionally, the a priori hypothesized correlations of changes over time of the MDADI domains to selected domains of the EORTC QLQ C30 and H&N35 were confirmed, where moderate correlations were found as expected, and with the strongest correlations to Social eating and Swallowing.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, at all study occasions, the difference between the patients and the control group without dysphagia exceeded the suggested threshold (10 points) indicating a clinically important difference 15 . These results are in line with other studies of patients with HNC, where patients with oral and oropharyngeal tumors demonstrated similar values of the MDADI and with a similar pattern of change over time 12,19‐23 . Additionally, the a priori hypothesized correlations of changes over time of the MDADI domains to selected domains of the EORTC QLQ C30 and H&N35 were confirmed, where moderate correlations were found as expected, and with the strongest correlations to Social eating and Swallowing.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, unlike previous studies that reported factors such as, age [16,18,19], marital status [46], and smoking [16][17][18] and deterioration in swallowing function through time [17,37,38], no associations were observed between age, smoking habit, marital status, time since diagnosis and type of carcinoma in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Factors predictive of poor quality of life (QoL) due to dysphagia could be patient-related [15] such as smoking [16][17][18], alcohol abuse [16], age [16,18,19], lean mass [16], and gender [16,19,20]; tumorrelated [15] such as advanced tumor stage [17,[21][22][23][24], location of HNC [25], such as patients with tongue [26], buccal [27], hypo pharyngeal [28] and laryngeal [29] tumors had worse dysphagia related QoL, type of treatment [15,25,30] in which higher level of dysphagia and lower QoL scores among patients who had radiotherapy [19], [31], [32], [29,33] and surgery [19,34,35] and patients treated with concomitant chemotherapy have an exacerbated dysphagia and dietary problems [36]. Deterioration in swallowing function through time were also reported from before treatment to 3 months [3,37,38] and 6 months [17,39] post treatment with some improvements at later times [17,37,38,…”
Section: Introductionmentioning
confidence: 99%
“…Our results were consistent with prior studies that identified the negative impact of cancer stage and location on swallowing related QoL. It is interesting to note that worse MDADI scores among patients with advanced tumor stages and had hypopharyngeal tumors observed in prior studies [10,23,24]. The literature results were consistent with the risk observed for lower QoL scores in our population.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of patients in this study reported that their swallowing limits their daily activities. The composite MDADI mean scores in this study were considerably lower than reported in Brazil (63.36) [3,23,24], the USA (64.06 and 67) [10,23,24], and Taiwan (67.08) [25], indicating the severity of this problem in Ethiopia. The variation may be due to the fact that patients in Ethiopia lack access to early treatment and support since there is a single cancer center in the country that provides comprehensive cancer care.…”
Section: Discussioncontrasting
confidence: 73%